Proposta de consolidação do processo de descentralização da execução orçamentária e financeira da UFSCAR - Alcoforado, Izaura do Carmo (2017)
Federal University of São Carlos – UFSCar, started in 2007 a decentralization process that initially led to the implementation of the Sorocaba Campus, such as the implementation and significant enlargement of the undergraduate courses in all campuses, as well as, recently, the implementation of a new campus – Lagoa do Sino Campus. Thus, the administration of UFSCar has been adapting to this new reality. This paper presents a proposal for advancement in the process of consolidation of the budget and financial execution of UFSCar. The decentralization of these activities effectively began in 2013, with the implementation of the commitment emission process in several campuses. For the development of this study, we carried out an extensive bibliographic survey, among other subjects, on centralization and organizational decentralization, budgetary and financial execution in the public sector, budgetary and financial decentralization in the public sector, in order to identify the main elements that could contribute to the objective of the work. Regarding the research methodology, it has a qualitative approach, such as a case study, which relied on the process of data collection through the application of questionnaires to those responsible for the related activities. In addition, we seek to consider specific aspects of UFSCar, such as: lean staff, the expansion that the institution has undergone, etc. The proposal presented at its core considers the creation of a control unit for UFSCar as a whole, as well as the creation of responsible and executive management units for all campuses. The expectation is that, with the implementation of this proposal, the UFSCar community as a whole will gain, among other benefits, speed in the respective processes and better monitoring and disclosure of the budget and financial execution of UFSCar.